Optimalisasi Pembelajaran Guru MI Muhammadiyah Panican Purbalingga Melalui Pelatihan Mind Mapping - Nayla Desviona; Rifki Chandra Utama; Luthfannisa Afif Nabila; Chairil Hikayat; Juwita Dien Maulida (Yayasan Pendidikan Penelitian Pengabdian Algero, 2024)
Education plays a vital role in human life as it is expected to enhance the nation's intelligence. The development of creative thinking in students is influenced by the encouragement or motivation provided by teachers. This ability can grow when teachers effectively stimulate students' creative thinking processes. Therefore, it is important for educators to innovate their teaching strategies to maintain student motivation. One method that can maximize the brain's potential and foster creativity is mind mapping. At MI Muhammadiyah Panican Purbalingga, many teachers still use traditional teaching methods. To address this, a training program focusing on practical mind mapping was implemented. The primary goal of this activity was to enhance the teachers' understanding of mind mapping as a tool to support learning. The training provided teachers with insight into how this method can improve lesson delivery and foster student creativity. The results showed that teachers were enthusiastic about participating, and some were already aware of the benefits of mind mapping in enhancing learning. This highlights the importance of conducting further mind mapping training to help teachers develop more effective and creative lesson plans. Additional support and motivation from government stakeholders are essential to advance the development of these educational activities.